A High‐Performance Membraneless Microfluidic Microbial Fuel Cell for Stable, Long‐Term Benchtop Operation under Strong Flow. Issue 10 (22nd April 2020) - Amirdehi, Mehran Abbaszadeh; Khodaparastasgarabad, Nastaran; Landari, Hamza; Zarabadi, Mir Pouyan; Miled, Amine; Greener, Jesse
Abstract: Invited for this month's cover picture is the group of Jesse Greener at Laval University in Quebec City (Canada). The cover picture shows a real microfluidic microbial fuel cell (MFC) used in this study. Three graphical elements are superimposed to highlight critical design enhancements over previous literature examples. These include: i) improved anaerobic environment with an oxygen protection barrier, ii) robust and kinetically favorable graphite electrodes, and iii) reduced anolyte/catholyte cross‐over to opposite electrodes via computer‐optimized device architecture. Bringing these improvements together into the same platform, we demonstrate an opportunity to bridge the gap between the micro‐ and macro‐MFC studies. Read the full text of the Article at 10.1002/celc.202000040 . Abstract : "A membraneless microfluidic microbial fuel cell is presented, which features a strictly anaerobic environment and robust graphite electrodes with optimized placement that avoid cross‐contamination between electrode compartments. The result is stable operation for six months for a pure Geobacter sulfurreducens biofilm, even under high flow rates…" Learn more about the story behind the research featured on the front cover in this issue's Cover Profile. Read the corresponding Article at 10.1002/celc.202000040 .